Innate Lymphoid Cells and Myocardial Infarction - Yang, Wenling; Lin, Jibin; Zhou, Jin; Zheng, Yuqi; Jiang, Shijiu; He, Shaolin; Li, Dazhu (Frontiers in Immunology, 2021)
Myocardial infarction is a coronary artery obstruction that causes insufficient blood supply to the myocardium and leads to ischemic necrosis. It is one of the main diseases threatening human life and health with high morbidity and mortality. Atherosclerosis is the pathological basis for the occurrence and development of myocardial infarction, and its pathogenesis has not been fully elucidated. Innate lymphoid cells are an important part of the human immune system and participate in processes such as immunity, metabolism, tissue development and remodeling. Studies have shown that Innate lymphoid cells are involved in the occurrence of atherosclerosis and play an important role. This review describes the relationship between Innate lymphoid cells and myocardial infarction in terms of the acute phase of myocardial infarction, myocardial ischemia-reperfusion injury, and regeneration and repair after myocardial infarction, in order to provide new potential intervention targets and new ideas for the treatment and prevention of myocardial infarction.